Inkcitha nzila nobomi obutsha (The release of the widow and life after mourning): Xhosa widows and citizenship - Jimlongo, Gcotyelwa Nomxolisi (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
This study examines the everyday conceptions and navigations of citizenship by Xhosa widows. It examines widows' own understandings and experiences of citizenship once the official mourning period, known amongst amaXhosa as ukuzila, has ended. The study draws from 14 interviews with Xhosa widows from the Amalinda, Tsholomnqa, Mdantsane, Magcumeni, KwaNonkcampa, and Dimbaza areas in the Eastern Cape, South Africa. This thesis contextualises claims to widowhood in the context of democratic South Africa, and the various ways in which widowed women conceptualise their lives after ukuzila. While ukuzila itself is written about in the literature, the contentious claims to widowhood and the ways in which women come to make sense of their lives in the post-mourning period remains largely unexplored. Interviews were conducted with women who had undertaken customary and/or civil marriages, had divorced or separated from their partners, or had cohabited. They reveal that widowhood is tenuous and as such, remains contested and contestable. The study demonstrates that much of the claims to widowhood are made because of the undeniable labour that women perform during the partnerships, where they are the primary economic providers. The study shows that whether in the formal and informal sector, women have been central in building the economic livelihoods of their families. In the post-mourning period, the theme of ukuhlala (to stay) that is articulated by widows, shows that they choose to remain in their marital homes to protect what they have laboured for. The findings demonstrate that the key to 'good' widowhood is intricately linked to 'good' motherhood. For Xhosa widows, much of their decision-making, and livelihood strategies, rests on how they craft good livelihoods for their families. These include a negotiation of feminist economies with woman-centred networks, a reliance on spirituality, as well as negotiations for dignity and respect within the homestead through the protection and maintenance of what they have built over the years.
Keywords: Widows -- South Africa -- Eastern Cape; Women, Black -- South Africa -- Eastern Cape; Xhosa (African people) -- South Africa -- Eastern Cape; Widows Social conditions; Widowhood Psychological aspects -- South Africa -- Eastern Cape; Widowhood Economic aspects -- South Africa -- Eastern Cape; Widowhood Social aspects -- South Africa -- Eastern Cape; Mourning customs -- South Africa -- Eastern Cape; Feminist economics -- South Africa -- Eastern Cape